SARS-CoV-2 in Childhood Cancer in 2020: A Disease of Disparities. Issue 34 (1st December 2021) - Johnston, Emily E.; Martinez, Isaac; Davis, Elizabeth S.; Caudill, Caroline; Richman, Joshua; Brackett, Julienne; Dickens, David S.; Kahn, Alissa; Schwalm, Carla; Sharma, Archana; Patel, Pratik A.; ,; et al.
Abstract : PURPOSE: The Pediatric Oncology COVID-19 Case Report registry supplies pediatric oncologists with data surrounding the clinical course and outcomes in children with cancer and SARS-CoV-2. METHODS: This observational study captured clinical and sociodemographic characteristics for children (≤ 21 years) receiving cancer therapy and infected with SARS-CoV-2 from the pandemic onset through February 19, 2021. The demographic and clinical characteristics of the cohort were compared with population-level pediatric oncology data (SEER). Multivariable binomial regression models evaluated patient characteristics associated with hospitalization, intensive care unit (ICU) admission, and changes in cancer therapy. RESULTS: Ninety-four institutions contributed details on 917 children with cancer and SARS-CoV-2. Median age at SARS-CoV-2 infection was 11 years (range, 0-21 years). Compared with SEER, there was an over-representation of Hispanics (43.6% v 29.7%, P < .01), publicly insured (59.3% v 33.5%, P < .01), and patients with hematologic malignancies (65.8% v 38.3%, P < .01) in our cohort. The majority (64.1%) were symptomatic; 31.2% were hospitalized, 10.9% required respiratory support, 9.2% were admitted to the ICU, and 1.6% died because of SARS-CoV-2. Cancer therapy was modified in 44.9%. Hispanic ethnicity was associated with changes in cancer-directed therapy (adjusted risk ratio [aRR] = 1.3; 95% CI, 1.1 to 1.6]). Presence of comorbidities was associated with hospitalization (aRR = 1.3; 95% CI, 1.1 to 1.6) and ICU admission (aRR = 2.3; 95% CI, 1.5 to 3.6). Hematologic malignancies were associated with hospitalization (aRR = 1.6; 95% CI, 1.3 to 2.1). CONCLUSION: These findings provide critical information for decision making among pediatric oncologists, including inpatient versus outpatient management, cancer therapy modifications, consideration of monoclonal antibody therapy, and counseling families on infection risks in the setting of the SARS-CoV-2 pandemic. The over-representation of Hispanic and publicly insured patients in this national cohort suggests disparities that require attention. Abstract :